Tulipa albanica (Liliaceae), a new species from northeastern Albania - Shuka, L.; Tan, K.; Siljak-Yakovlev, S. (Phytotaxa, 2014)
Tulipa albanica (Liliaceae) is illustrated and described as a new species from a serpentine area in Kukesi district, northeastern Albania. It is compared with T. scardica from the western Balkans (Macedonia and Kosovo) and with T. schrenkii from the Ukraine, Caucasus, Central and Southwest Asia. The chromosome number, karyotype features and nuclear DNA content (2C-value) were assessed by karyological and flow cytometry techniques and provided for the first time for this species. The chromosome formula is 2n = 2x = 24 (2 metacentric, 3 submetacentric and 7 subtelocentric chromosome pairs) and the genome size 54.15 (+/- 0.23) pg. Two different morphotypes of T. australis were noted as occurring on limestone or serpentine in Albania.